Generalized Anxiety Disorder among Paediatricians During the COVID-19 Pandemic - Aziz, Shaffaq; Shabir, Sadia; Noor, Misbah; Samaa, Asvar; Aslam, Samia; Hamid, Muhammad Haroon (Annals of King Edward Medical University, 2024)
Background: COVID-19 pandemic has put healthcare professionals at risk of developing mental health issues. Primarily, because of their increased chances of being affected and fulfilling their job commitments despite insufficient knowledge about the new disease and its management. Hence, it is essential to assess the burden of such mental health issues amongst healthcare providers. Objective: To determine the frequency and severity of generalized anxiety disorder among paediatricians during the COVID-19 pandemic. Methods: Cross-sectional observational study conducted in Department of Paediatrics (unit 1), King Edward Medical University/ Mayo Hospital Lahore, duration of 03 months. After IRB approval, an online survey form was developed based on GAD-7 Scale as an assessment tool for assessing anxiety among paediatricians. A survey form was dispersed using social media to pediatricians of different ages and working statuses. The responses were recorded and assessed using SPPSS. Quantitative variables (age, GAD-score) were summarised as mean and standard deviation. Qualitative variables (gender, place of work, individual GAD- component score) were summarised as frequency and percentages. Results: A total of 147 responses were received, out of which 13 were excluded. The remaining 134 were analysed through SPSS 26. Out of these, 106 (79.1%) turned out to be suffering from new-onset anxiety. Amongst these 106 paediatricians, 69 (65.1%) were females, and 37(35.9%) were males (p-value 0.013). The severity of anxiety was mild, moderate and severe in 62 (46.3%), 37 (27.6%) and 7 (5.2%) of paediatricians, respectively. Conclusion: More than three-fourths of paediatricians had higher GAD 7 scores during the COVID-19 pandemic suggesting generalized anxiety disorder.